Invisible stripes [videorecording (DVD)] - Bacon, Lloyd, 1890-1955; Raft, George; Bryan, Jane, 1918-2009; Holden, William, 1918-1981; Bogart, Humphrey, 1899-1957 (Warner Bros. Pictures gangsters, 2008)
Chuck Martin is going straight when he gets out of the big house - straight back into a life of crime. In lockup or out in the civilian world, he knows that he will forever wear a con's invisible stripes. Martin's ex-Sing Sing yardmate Cliff Taylor, vows to walk away from crime and be a role model for his kid brother. What awaits Taylor are suspicion, public disdain and joblessness. He turns to a fellow con for help. Crime doesn't pay, but it does have a price.